Cooperative Multi-channel Dissemination of Safety Messages in VANETs - Steven Eyobu, Odongo; Joo, Jhihoon; Seog Han, Dong (IEEE, 2016)
IEEE 802.11p-based wireless access in vehicular environments (WAVE) multi-channel communication introduces communication clusters which limits on the dissemination efficiency of broadcast applications such as safety messaging. This paper proposes cooperative multi-channel information dissemination (CMD) which follows a channel coordination approach where the coordinator is selected based on the least average distance (LAD) to all service channels with the goal of relaying the emergency message to other service channels with minimum delay. On receipt of high priority emergency messages, each selected channel coordinators switches to a defined service channel and broadcasts the emergency message to it members. In the CMD approach, each vehicle assumes a single radio and the number of channel coordinators in each service channel cluster is determined based on the available service channels advertised and LAD to the advertised service channels. Computer simulations show that the proposed CMD performs well in terms of dissemination delay and dissemination rate.
Keywords: IEEE 802.11p/WAVE; Vehicular ad hoc networks; Channel coordination; Cooperative message dissemination